Policy Innovations: Applied political economy and governance tools for decision making and inclusion - Kyle, Jordan; Mockshell, Jonathan; Kaaria, Susan; Ngeno, Evans; Resnick, Danielle (CGIAR System Organization, 2025)
The legitimacy and sustainability of many policy decisions hinges on who participates and how trade-offs across different goals are managed. In this joint CGIAR Policy Innovations Program and Gender Equality and Inclusion Accelerator webinar, two new tools will be shared to help policy makers, researchers and practitioners recognize viable entry points into the policy process and whose voices are included or excluded. The first is the Political Economy and Policy Analysis (PEPA) simulation tool, which utilizes artificial intelligence (AI) functions to identify the appropriate analytical framework for addressing priority policy questions and integrating different stakeholder viewpoints. The second is the Women’s Empowerment in Agrifood Governance (WEAGov) tool, which uncovers the extent that women are empowered to engage at different stages of the policy process, from agenda setting and design, implementation, and evaluation. Examples of applications from these tools and their implications for policymaking will be shared by the presenters and discussed by experts.